2018
DOI: 10.1097/md.0000000000011243
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic macular hole with asteroid hyalosis

Abstract: Introduction:Asteroid hyalosis (AH) is characterized by mild vitreous-body liquefaction and a reduced likelihood of posterior vitreous detachment (PVD). Here, we report the clinical features of 2 cases of macular hole (MH) in eyes with AH. The extent of retinal vitreous adhesion at the time of vitreous surgery, the presence or absence of iatrogenic retinal breaks, and the postoperative course was examined in regard to the association with AH.Case presentation:Case 1 involved a 67-year-old female with decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, both cases had relatively loose and easy to peel adhesions around the macular hole, allowing for successful closure of the fullthickness macular hole. 5 More recently, Rahman et al discussed the complexities of macular hole repair in a patient with adhesions from proliferative diabetic retinopathy and hyaloid attachments from asteroid hyalosis. Similar to the other reports, the area of hyaloid around the macular hole was able to be released from the adhesions with ease, leading to successful macular hole repair.…”
Section: Discussionmentioning
confidence: 99%
“…However, both cases had relatively loose and easy to peel adhesions around the macular hole, allowing for successful closure of the fullthickness macular hole. 5 More recently, Rahman et al discussed the complexities of macular hole repair in a patient with adhesions from proliferative diabetic retinopathy and hyaloid attachments from asteroid hyalosis. Similar to the other reports, the area of hyaloid around the macular hole was able to be released from the adhesions with ease, leading to successful macular hole repair.…”
Section: Discussionmentioning
confidence: 99%
“…Kitagaki et al [ 9 ] presented two cases of idiopathic macular hole with AH. They performed standard phacovitrectomy and observed very strong vitreoretinal adhesion starting at the mid-periphery, resulting in multiple iatrogenic tears during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These adhesions probably enhance with coexisting maculopathy or proliferative diabetic retinopathy. It has been reported that there is an increase in inflammation-related cells, such as macrophages, in the vitreous of AH and that prolonged mild inflammation might accelerate the manifestation of the adhesion molecules at the vitreoretinal interface [9]. Kitagaki et al [9] presented two cases of idiopathic macular hole with AH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation